Linear convolution using UT Vedic multiplier - Hari Kishore, K; Noorbasha, Fazal; Sandeep, Katta; N. V. Bhupesh, D; Khadar Imran, SK; Sowmya, K (International Journal of Engineering and Technology, 2018)
Linear Convolution is one of the elemental operations of Signal processing systems and is used by some Multiplication Algorithms. In our project we perform Linear Convolution using ancient Multiplication Algorithm called UrdhvaTriyagbhyam (UT) which is one among the 16 sutras in Vedic mathematics. This provides best results in speed when compared to other multipliers. UrdhvaTriyagbhyam technique is used to increase the timing performance of the design. Our aim is to design 8 bit convolution using UT. The synthesis and simulation is done by using XILINX ISE Design.